The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/clc.22799
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mid‐ to long‐term clinical outcomes between anatomical testing and usual care in patients with suspected coronary artery disease: A meta‐analysis of randomized trials

Abstract: Anatomical testing with CCTA as the initial noninvasive diagnostic modality in patients with suspected CAD resulted in lower risk of nonfatal MI than usual care with functional testing, at the expense of more frequent use of invasive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Current strategies have focused on anatomical imaging with coronary computed tomography angiography (CCTA) with or without fractional flow reserve measurement (CCTA-FFR) and functional methods including stress ECG, stress echocardiography, and myocardial perfusion imaging (MPI) with ionizing radiation along with emergence of hybrid imaging of positron emission tomography (PET) together with CT (cardiac PET-CT). In outcomes analysis, direct coronary imaging with CCTA has shown reduced myocardial infarction (MI) compared with functional testing but without a reduction in mortality or hospitalizations at the expense of more frequent use of invasive procedures [ 2 ▪ , 3 , 4 ▪ ]. With the growing challenge of symptomatic nonobstructive CAD (NO-CAD) in clinical practice, these modalities have limited value.…”
Section: Introductionmentioning
confidence: 99%
“…Current strategies have focused on anatomical imaging with coronary computed tomography angiography (CCTA) with or without fractional flow reserve measurement (CCTA-FFR) and functional methods including stress ECG, stress echocardiography, and myocardial perfusion imaging (MPI) with ionizing radiation along with emergence of hybrid imaging of positron emission tomography (PET) together with CT (cardiac PET-CT). In outcomes analysis, direct coronary imaging with CCTA has shown reduced myocardial infarction (MI) compared with functional testing but without a reduction in mortality or hospitalizations at the expense of more frequent use of invasive procedures [ 2 ▪ , 3 , 4 ▪ ]. With the growing challenge of symptomatic nonobstructive CAD (NO-CAD) in clinical practice, these modalities have limited value.…”
Section: Introductionmentioning
confidence: 99%
“…CAD is a spectrum of heart disease with the highest mortality rate in the world [10]. There is little information about LV dysfunction in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise Testing in Suspected Coronary Artery Disease (CRESCENT) [ 100 ] and the Cardiac CT for the Assessment of Pain and Plaque (CAPP) [ 101 ]. A meta-analysis including most of the above studies in patients with either acute or stable chest pain showed that anatomical testing with CCTA as the initial non-invasive diagnostic modality resulted in a lower risk of non-fatal myocardial infarction, but not MACEs or all-cause mortality, as compared with the usual care with functional testing at the expense of a more frequent use of invasive procedures [ 102 ]. Moreover, a systematic review in patients with acute or stable chest pain showed that CCTA is cost-effective when compared with the standard of care, including functional testing [ 103 ].…”
Section: Contrast-enhanced Ctmentioning
confidence: 99%